1996
DOI: 10.1063/1.117206
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of deep acceptor activation in semiconductors by superlattice doping

Abstract: Public reporting burden for this collection of information is estimated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(86 citation statements)
references
References 1 publication
0
85
0
1
Order By: Relevance
“…This provides a periodic oscillation in the valence band edge, allowing ionisation of acceptors in the wide bandgap AlGaN layers to provide hole accumulation in the adjacent GaN layers, leading to an overall increase in hole concentration [45]. The principle is illustrated in .…”
Section: P-type Dopingmentioning
confidence: 99%
“…This provides a periodic oscillation in the valence band edge, allowing ionisation of acceptors in the wide bandgap AlGaN layers to provide hole accumulation in the adjacent GaN layers, leading to an overall increase in hole concentration [45]. The principle is illustrated in .…”
Section: P-type Dopingmentioning
confidence: 99%
“…They argue that, as the electrically active acceptor concentration increases, the isolated deep acceptor levels begin to interact and split into an impurity band, which is closer to the valence band thus lowering the effective activation energy. Peter and Schubert 24,25 demonstrated another strategy and found that by polarization induced modulation of the valence band edge in a superlattice, the low doping efficiency could be partially overcome. Simon and Jena 26 also suggested that a 3D hole gas could be produced using the builtin electronic polarization in nitrides.…”
Section: Present Solution For P Doping Difficultiesmentioning
confidence: 99%
“…edge produced by a superlattice structure, such as AlxGa1-xN/GaN, can also modify the characteristics and energy position of the VBM. 31,32 Based on this consideration, a novel strategy for efficient p-type doping is proposed to overcome the fundamental problem of high activation energy by inducing impurity resonant states in an Mg doped AlxGa1-xN/GaN superlattice structure. As schematically shown in Fig.…”
Section: New Strategy Based On Band-engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…37,[134][135][136][137] Because of the SL structures, low-resistance ohmic contacts to pGaN/Al x Ga 1-x N was shown to form, producing specific contact resistivity ∼10 …”
Section: 99mentioning
confidence: 99%